Pendidikan dan Pelatihan Desain Pengembangan Video Pembelajaran Interaktif di SMAN Kembangbahu Lamongan - Chayatun Machsunah, Yayuk; Youhanita, Ety; Nurdiana, Ratna; Yuliani, Endah (Academia Publication, 2021)
This service activity aims to provide education and training for teachers at SMA Negeri Kembangbahu, Lamongan regency on making learning media by designing interactive videos. This is because video besides being used as entertainment media can also be used as a medium for education / learning. The method used is exposure (lectures) and direct practice by changing the power points that have been very familiar to the teacher in delivering material directly to students into interactive videos so that the learning material will be more interesting